STEGANOGRAFI DENGAN AES PADA MEDIA SUARA BERBASIS INTERNET - Rifki Indra Perwira (Telematika, 2020)
Information is an important part of the current era. Information has become a necessity so as not to be left behind by the times. By utilizing information, ideas and innovations will emerge. This information can be used for the benefit of many people. The more developed means of communication, the more the use of information is also developing. With the increasing number of ways to access this information, we need an application that can be used to secure information by storing information in containers such as sound, so that information can not be known by others. Steganography is a file hiding technique that becomes confidential so that other people do not understand the secret message that is in it. Cryptography is the science and art of secure messages. Utilizing sound as a media to insert secret messages, as well as adding cryptography as a security message secret before being inserted, so that the process of transferring information can be done safely. The results of this study steganography techniques can be used in sound. By inserting a text message that is first encrypted and then entered into sound by the Least Significant Bit method.